Introduction to airborne radar - Stimson, George W. (SciTech Pub., 1998)
An introduction to the subject for non-specialists: engineers, technicians, pilots, and aerospace industry marketing, public relations, and customer support personnel. Also a reference for specialists in the field. The completely rewritten and revised Second Edition updates the original published by the Hughes Aircraft Company.
Keywords: Airplanes -- Radar equipment.; elektronické knihy; electronic books